Sex - Hatch, Ryan Anthony (Filozofski vestnik, 2025)
This essay sets out from the observation that, by and large, the Lacanian field has tend-ed to celebrate Joan Copjec’s “Sex and the Euthanasia of Reason” at the expense of rig-orously engaging with it. Indeed, Copjec’s explosive text has often been taken—wrong-ly—as warranting both an indiscriminate dismissal of the entire project of queer theory (especially where it contests psychoanalytic theorizations of sexual difference) and the frequent confusion of transphobic countertransference with psychoanalytic thinking. Moving against this tendency, “Sex: Trouble” disencumbers the queer- and trans-eman-cipatory kernel of Copjec’s argument—that is, that sex serves no other purpose than to serve no purpose—from the dimorphic and sometimes “cisnormative” terms through which this radical kernel is at once elaborated and undermined. Setting “Sex and the Euthanasia of Reason” in dialogue with a number of queer and trans theorists, “Sex: Trouble” establishes Copjec’s thought as an indispensable weapon in the struggle against the profusion of meanings that threaten to obliterate the negativity, the nothing, that sex is, and on which the freedom of queer and trans (read: all) subjects is staked.
Keywords: gender; psihoanaliza; psychoanalysis; razlika med spoloma; sexual difference; spol